THEORETICAL ASPECTS OF MONEY LAUNDERING AND ITS IMPACT ON THE ECONOMY - I. Voronin (Вестник Северо-Кавказского федерального университета, 2022)
Money laundering is a worldwide phenomenon with global social, political and economic consequences. The existence of illegal flows generates economic transformations, such as the indiscriminate use of resources, reduced investment in the economy, a weakening of the banking sector, and increased corruption. Therefore, it is very important for the state to know the scale and consequences of money laundering for the economy, as well as to understand what needs to be done to combat this phenomenon. Currently, financial and credit institutions really care about compliance with the requirements of anti-money laundering legislation in order to prevent harsh sanctions from the regulator and loss of reputation. And the Government, in turn, must clearly monitor the economic and financial flows, both within the country and going abroad, so that the country's economy does not turn into a «laundry» of a global scale.